“mejoramiento de la etapa de prensado en el proceso de elaboración de harina de pescado mediante un sistema automatizado de control de la humedad en la empresa jada s.a. – chimbote” - Cárdenas De La Cruz, Arturo Giancarlos. (2016)
This thesis aims to design a method of controlling moisture in pressing for plant JADA S.A. to obtain a press cake moisture within acceptable ranges, where a relationship between humidity and screw speed press shown. In Chapter 1 Introduction of the thesis which describes the problem. problems such as high times, fluctuations in the data and maintenance costs and rework are identified. In Chapter 2 basics of the different parts that make up the design of automatic humidity control, and some important parameters to be taken into account are detailed. Chapter 3 information on various current methods of moisture control and procedures to be followed in the press is collected. Then we determine the most suitable method for controlling moisture in the press that can be implemented at the plant JADA S.A. evaluating three options, using an array of selection based on some design criteria, obtaining the PID control the highest score. We determine the components for our system, according to our requirements. Finally, we present a mathematical analysis of the system proposed theoretical and experimental pressing, with a simulation of the equations obtained. Chapter 4 presents the results of a simulation approximate transfer functions of the system experimentally obtained by applying the PID control and note that diminish rise and establishment of the control system of moisture in the press. Moreover, the application of the proposed automation in a prototype system. Finally in Chapter 5 results conclusions of the thesis among which are a determining factor in the quality of the raw material, in addition to the results of a prototype system our proposal automation can be carried to other cases control first order systems, PID control is shown as the best alternative solution the system but intends to implement other types of control such as PI control to compare our results.